2018
DOI: 10.3389/fmicb.2018.02207
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Biosynthesized Silver and Zinc Nanoparticles Against Multi-Drug Resistant Pathogens

Abstract: Biosynthesis of metallic nanoparticles has acquired particular attention due to its economic feasibility, low toxicity, and simplicity of the process. In this study, extracellular synthesis of silver and zinc nanoparticle was carried out by Pseudomonas hibiscicola isolated from the effluent of an electroplating industry in Mumbai. Characterization studies revealed synthesis of 40 and 60 nm nanoparticles of silver (AgNP) and zinc (ZnNP), respectively, with distinct morphology as observed in TEM and its crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 24 publications
1
58
1
1
Order By: Relevance
“…Although there is a lower bacterial population, SEM images from PB and SB revealed no changes in bacteria morphology in the three treatments analyzed (Figs 2 and 4). It is important to mention the low toxicity found for ZEO-CuNPs and ZEO-ZnNPs, whose antimicrobial effects as zero-dimensional metallic nanoparticles are well documented [34,35]. The oxidation state of the CuNPs and ZnNPs within the zeolite matrix seems to be fundamental for its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a lower bacterial population, SEM images from PB and SB revealed no changes in bacteria morphology in the three treatments analyzed (Figs 2 and 4). It is important to mention the low toxicity found for ZEO-CuNPs and ZEO-ZnNPs, whose antimicrobial effects as zero-dimensional metallic nanoparticles are well documented [34,35]. The oxidation state of the CuNPs and ZnNPs within the zeolite matrix seems to be fundamental for its antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the broad‐spectrum antimicrobial activity of silver nanoparticles, including the drug‐resistant S. aureus , K. pneumonia , E. coli , E. faecalis , P. aeruginosa , A. baumannii , and M. tuberculosis . The silver nanoparticles synthesized with AgNO 3 and leaf extract of Annona reticulata showed potent activity against Bacillus cereus and Staphylococcus aureus at 125 and 31.25 μg/mL; while it inhibits Escherichia coli , Pseudomonas aeruginosa and Candida albicans at 62.5 μg/mL .…”
Section: Discusssionmentioning
confidence: 99%
“…The image also showed the damaged cell wall (pores) and cell membrane leading to the leakage of cytosolic content to lysis, compared to the untreated bacteria with normal rod‐shaped morphology, due to the differences in their sensitivity pattern (MIC 0.50 and 0.60 μM), along with variations in inoculum size, resistance level, peptidoglycan, biochemical and molecular structure as well as other components. Further, nanoparticles not only act on bacteria by direct contact, but also penetrate rapidly to interact with microbial DNA, that prevents the bacterial to develop resistance, and thus nanoparticles are less disposed to bacterial resistance . This suggests that Ag‐NP‐AE can be helpful in the management of those MDR‐bacterial infections.…”
Section: Discusssionmentioning
confidence: 99%
“…Silver nanoparticles seem to be effective against drug-resistant strains of Methicillin-resistant staphylococcus aureus, extended-spectrum beta-lactamases, vancomycin-resistant enterococcus, and multi-drug resistant Pseudomonas aeruginosa. Therefore, it provides a potential antimicrobial effect against all drug-resistant strains and has a viable therapeutics candidate [23].…”
Section: Application In Multi-drug Resistant Therapymentioning
confidence: 99%